헤파린 처리된 개에서 급성 폐동맥 고혈압이 프로타민의 혈압하강작용에 미치는 영향 - 유경연; Kyung Yeon Yoo; 심승진; Seung Jin Shim; 박종은; Jong Eun Park; 임웅모; Woong Mo Im (Korean journal of anesthesiology, 1998)
Introduction : The present study was aimed to investigate the hemodynamic effects of protamine and to determine whether the increases of pulmonary arterial pressure(△PAP) after protamine is related to development of systemic hypotension in heparinized dogs. Methods : Nineteen mongrel dogs were acutely instrumented during 1.5% halothane anesthesia. All dogs then received protamine 3 mg·kg 1 over a period of 30 s given through right atrium 5 minutes after heparin(300 IU·kg-1, iv). Animals were retrospectively assigned into two groups, control(△PAP＜6 mmHg, n=9) and pulmonary hypertensive(PHT, △PAP＞6 mmHg, n=10) groups. Mean arterial pressure(MAP), mean pulmonary arterial pressure(MPAP), left ventricular pressure, heart rate(HR), and cardiac output and left circumflex coronary flow(LCX flow) via Doppler flowmeter were continuously recorded throughout the experiments. Changes in MPAP were related to changes in MAP using standard regression analysis. Results : MPAP(66% in PHT vs 7% in control group) and pulmonary vascular resistance index(5.1- vs 3.0-fold) increased more markedly immediately after protamine administration in PHT group than in control group. However, protamine caused similar reductions of MAP(-40 vs -46%), cardiac index(-60 vs -59%), and left ventricular end- diastolic pressure(-47 vs -53%) in both groups. No correlation was found between △PAP and △MAP in either group. LCX flow increased significantly but similarly immediately after protamine in both groups(183 vs 238%), indicating rapid release of potent vasodilator. Conclusions : These results suggest that, in heparinized dogs, protamine produces transient severe hypotension but does not consistently elevate pulmonary arterial pressure and, that acute pulmonary vasoconstriction does not play a major role in protamine-induced hypotension. (Korean J Anesthesiol 1998; 35: 404∼412)